Resilience and Agility of Education Support Staff: Transforming Communities of Practice toward a Sustainable Digital Learning Ecosystem - Moh. Ainul Yaqin; Ahmad Syaikhul Yasin; Ahmad Munawir; Siti Aimah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
This study analyzes strategies for transforming communities of practice (CoP) to build resilience and agility among education support staff (tenaga kependidikan) and to conceptualize a sustainable digital learning ecosystem in the Indonesian educational context. A systematic literature review design was employed, integrating a policy document analysis approach. Literature was retrieved from Google Scholar, ERIC, and Scopus databases using the keywords community of practice, education support staff, resilience, organizational agility, digital learning ecosystem, and knowledge management. Inclusion criteria covered peer-reviewed articles from 2015 to 2025 relevant to professional development, digital transformation, and knowledge management in educational organizations; 42 peer-reviewed articles and 8 national policy documents were analyzed using thematic synthesis following Thomas and Harden (2008). The synthesis of literature indicates that CoP reinvigoration grounded in collaborative technology holds strong potential to accelerate the adaptability of education support staff in the face of rapid technological disruption. Evidence from the reviewed literature suggests that individual resilience is enhanced when supported by a collective culture that facilitates digital experimentation and data literacy. Furthermore, CoP-based peer learning models appear to improve the responsiveness of education support staff to institutional dynamics. This study offers a theoretical contribution to human resource management models in the education sector and proposes a conceptual framework for policymakers to design competency development programs that address both technical competencies and the sustainability of collaborative learning ecosystems. Research limitations include the absence of primary field data and the lack of empirical comparison with alternative HR development models.